Icariin, the main prenylflavonoid of Epimedii Folium, ameliorated chronic kidney disease by modulating energy metabolism via AMPK activation. (10th August 2023) - Zhao, Yudan; Yang, Wanyue; Zhang, Xin; Lv, Chongning; Lu, Jincai
Abstract: Ethnopharmacological relevance: Epimedii Folium is a famous traditional Chinese medicine (TCM) widely used in classic formulas, Chinese patent drugs and health care products for treating kidney diseases. Therefore, we speculated that icariin, its main component, might also have a good therapeutic effect on chronic kidney disease (CKD). Aim of study: To investigate the efficacy and potential mechanism of icariin on CKD. Materials and methods: A CKD model was established by intragastric administration of adenine (200 mg/kg/d) to adult male SD rats for 28 consecutive days. TGF-β1-induced fibrotic HK-2 cells were applied to establish the renal fibrosis model in vitro. Biochemical determination, pathological staining, flow cytometry and ELISA were performed to preliminarily evaluate the renoprotection of icariin. The intervention effect of icariin on renal fibrosis progression was assessed by cell stiffness determination and multiple immunological methods. The potential mechanism of icariin on CKD was revealed by means of 1 H NMR metabolomics, qRT-PCR and Western blotting analysis. Results: Icariin at the dosage of 100 mg/kg/d and 200 mg/kg/d markedly ameliorated rat renal function in a dose-dependent manner. Based on renal pathological features, the mechanism of icariin intervention in CKD was initially revealed by metabolomics, which was closely related to energy metabolism pathways. Furthermore, the detection results of AMPK and related factors in its mediated signaling pathways indicated that icariin exerted a therapeutic effect on CKD by attenuating inflammation and oxidative stress responses and retarding renal fibrosis progression through regulating AMPK/SIRT1/NF-κB and AMPK/ACC signaling pathways. Conclusion: It was the first time to demonstrate that icariin could treat adenine-induced CKD by modulating energy metabolism via AMPK activation in a dose-dependent manner. Graphical abstract: Image 1 Highlights: Icariin, as the main bioactive prenylflavonoid of Epimedii Folium, displayed a good therapeutic effect on CKD. Metabolomics was adopted based on the kidney disease features to reveal the mechanism of icariin on CKD. Icariin ameliorated CKD by regulating AMPK/SIRT1/NF-κB and AMPK/ACC signaling pathways. AMPK activation by icariin could alleviate inflammation and oxidative stress and thereby retard renal fibrosis progression..